2010
DOI: 10.1177/1012690210378273
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuating the ‘lack of evidence’ discourse in sport for development: Privileged voices, unheard stories and subjugated knowledge

Abstract: Through an examination of the power relations embedded in the international movement of sport for development, we consider the dominant ‘lack of evidence’ discourse, which calls for more rigorous, scientific proof to validate the sport for development field. We argue that the lack of co-creation of knowledges, the politics of partnerships, and donor-driven priorities have subjugated sport for development practitioners’ knowledge, and therefore fueled this lack of evidence discourse. Acknowledging and privilegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 17 publications
1
118
0
3
Order By: Relevance
“…Yet, SDP monitoring and evaluation is implicated in the aforementioned power relations and donor bias, which extend to the realm of knowledge production. Recent research highlights the need to address issues of power and positionality in monitoring and evaluation, including the impact that Global North/Global South power imbalances have on data (Jeanes and Lindsey 2014), and how local voices and ways of thinking and knowing are marginalized in monitoring and evaluation in the SDP sector (Nicholls et al 2011). The latter has inspired critical scholars to call for the decolonising of monitoring and evaluation methodologies (Kay 2009), urging us to reflect on questions such as: Who develops, leads and controls monitoring and evaluation?…”
Section: Sdp Design and Implementationmentioning
confidence: 99%
“…Yet, SDP monitoring and evaluation is implicated in the aforementioned power relations and donor bias, which extend to the realm of knowledge production. Recent research highlights the need to address issues of power and positionality in monitoring and evaluation, including the impact that Global North/Global South power imbalances have on data (Jeanes and Lindsey 2014), and how local voices and ways of thinking and knowing are marginalized in monitoring and evaluation in the SDP sector (Nicholls et al 2011). The latter has inspired critical scholars to call for the decolonising of monitoring and evaluation methodologies (Kay 2009), urging us to reflect on questions such as: Who develops, leads and controls monitoring and evaluation?…”
Section: Sdp Design and Implementationmentioning
confidence: 99%
“…The contextual constraints appeared, in some cases, to challenge the students to develop new skills and students' increased awareness of constraints and inequalities in international development was also notable. Nevertheless, the knowledge and experience of Ghanaian students was subjugated to different degrees in the project, as has also been recognised in Nicholls et al's (2011) important paper. The position of both UK and Ghanaian students in the project meant that they were unable to challenge this subjugation even when they recognised and were morally challenged by it.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of contributing to wider analysis of North-South relations, this analysis points to the importance of responsibility for instigating projects. That the inexperience of some of the Northern stakeholders involved in the instigation of the project contributed, perhaps unintentionally, to power imbalances experienced by students is also resonant of other sport-for-development programmes (Nicholls et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Coalter (2010) has been critical in this regard suggesting that programs of SfD often conflate micro-level individual gains with community wide development and engage in narrowly framed interventions yet claim to be addressing what Coalter (2010) referred 6 to as 'broad gauge problems' (p. 308) that tend to lack clear targets for change. As a counterpoint, however, Nicholls et al (2010) demonstrated that ample data have emerged from well-structured programs that show demonstrable outcomes at the individual and community levels. That such outcomes gain little traction, Nicholls et al (2010) argued, is a consequence of the silencing of some research voices that tend to be both young and of colour.…”
Section: Introductionmentioning
confidence: 99%
“…As a counterpoint, however, Nicholls et al (2010) demonstrated that ample data have emerged from well-structured programs that show demonstrable outcomes at the individual and community levels. That such outcomes gain little traction, Nicholls et al (2010) argued, is a consequence of the silencing of some research voices that tend to be both young and of colour. Of significance for forums such as this journal, the prevailing conditions have contributed to a high degree of contestability regarding the academic terrain of SfD (Hartmann and Kwauk, 2011;Schulenkorf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%